The Reasons for Permission to Marry Ahlul Kitāb Women in the View of Sayyid Sabiq - Munir, Akmal Abdul; Mochammad Sahid, Mualimin; Zulkifli, Zulkifli; Fauzi, Ahmad (al-'adalah, 2021)
Marrying women from the people of the Book (ahlul kitāb) is a matter of dispute amongMuslim scholars, some allow it and some forbid it. Sayyid Sabiq is among the scholars who allows Muslim men to marry women of the People of the Book under strict requirements to avoid harm and negative impacts that will occur if the marriage is carried out. This paper discusses the law of Muslim men marrying women of ahlul kitāb (the People of the Book)and analyzes it from the perspective of Sayyid Sabiq. Based on the results of the study conducted, the authors found the fact that SayyidSabiq allowed Muslim men to marry ahlul kitābwomen based on the following considerations: (i) To eliminate barriers between ahlul kitāband Muslims. (ii) As a means to establish social relations and closeness between others so that they can provide space for non-Muslims to learn and know the truth of Islamic teachings. (iii) As a means to invite them to follow Islam